2009
DOI: 10.3855/jidc.410
|View full text |Cite
|
Sign up to set email alerts
|

Is cholera disease associated with poverty?

Abstract: Background: Cholera remains a global threat and is one of the key indicators of social development. While the disease no longer poses a menace to countries with minimum standards of hygiene, it remains a serious challenge to countries where access to safe drinking water and adequate sanitation cannot be guaranteed. The objective of this work was to analyse the results obtained when contrasting the reports of the World Health Organization (WHO) about cholera disease with those of the World Bank List of economie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 12 publications
1
37
0
Order By: Relevance
“…This study shows that low-income countries are more affected by cholera than those with medium or high incomes. This supports the phrase "cholera is a disease of poverty" [26]. A study conducted in Matlab, Banglandesh showed that the risk of cholera increased with low household income.…”
Section: Discussionsupporting
confidence: 64%
“…This study shows that low-income countries are more affected by cholera than those with medium or high incomes. This supports the phrase "cholera is a disease of poverty" [26]. A study conducted in Matlab, Banglandesh showed that the risk of cholera increased with low household income.…”
Section: Discussionsupporting
confidence: 64%
“…Alongside other diarrheal diseases, cholera is a major cause of preventable childhood and adult deaths in developing countries [31]–[32]. Given international attempts like the fourth millennium development goal (MDG) to reduce such burdens, it is surprising that cholera has not gained more public health attention.…”
Section: Discussionmentioning
confidence: 99%
“…On seasonal time scales cholera, as other diseases in Nigeria (e.g., Olouko et al, 2014), shows a seasonality with increased burdens from May to August. Additionally, social risk factors are playing an important role in transmission and outbreak of cholera, for example, the disease has been termed the 'disease of poverty' (Charles and Ryan, 2011;Snowden, 2008) and was associated with inadequate environmental sanitation conditions and untreated drinking water (e.g., Ali et al, 2002aAli et al, , 2002bHashizume et al, 2007;Penrose et al, 2010;Rajendran et al, 2011;Reiner et al, 2012;Talavera and Perez, 2009). Previous studies have demonstrated the possibility of predicting cholera epidemics (e.g., Reyburn et al, 2011), however, the importance of combining the effects of social risk factors in addition to meteorological conditions in studying the dynamics of the disease has been pointed out (e.g., Pascual et al, 2000;Chou et al, 2010).…”
Section: Introductionmentioning
confidence: 99%